Characterisation of 32P beta source for external radiation protection. (June 2016) - Vandana, S.; Bakshi, A.K.; Saxena, Sanjay Kumar; Chattaraj, Arghya; Palani Selvam, T.; Srivastava, K.; Dash, Ashutosh; Datta, D.
Abstract: Custom-made design of 32 P patch sources are used in brachytherapy applications. Use of this source requires external radiation protection. This implies measurement of absorbed dose rate to tissue at a depth of 0.07 mm. Towards this goal, 2.75 mCi 32 P patch source was locally developed. Characterization of this source has been carried out by measuring source parameters such as uniformity in the activity distribution and beam uniformity. The characterization also includes output measurements in terms of absorbed dose rate to air using an extrapolation chamber at 11, 20 and 30 cm from the source. Various correction factors which are dependent on the cavity length as well as independent of the cavity length were also determined in this study. The backscatter correction and Bragg–Grapy stopping power ratio were calculated using the Monte Carlo techniques. Using these correction factors and the measured absorbed dose rate to air, absorbed dose rate to tissue at a depth of 0.07 mm was determined. The study also includes measurements of Hp (0.07) and Hp (10) at different source-to-detector distances using an electronic pocket dosimeter. Highlights: 32 P patch source for external radiation protection. Characterization of source parameters such as activity and beam uniformity. Measurement of absorbed dose to tissue using extrapolation chamber. Determination backscatter factor and stopping power ratio using Monte Carlo technique. Measurement of Hp(10) and Hp(0.07) using electronic pocket dosimeter.